Numerical investigation on the thermal-flow performance of humid air-water in the interspace outside staggered tube bundles. (February 2021) - Ma, Hongqiang; Liu, Yemin; Hou, Caiqin; Wang, Gang; Luo, Xinmei
Highlights: A new model is established to analyze the thermal-flow performance of humid air-water outside staggered tube bundles. The main factors are obtained to impact the thermal-flow performance of humid air-water outside staggered tube bundles. New correlations of HSW and pressure drop are obtained in term of the simulation datum. A correlation is also recommended to design the mass transfer performance of humid air-water outside staggered tube bundles. Abstract: A new model was established to investigate the thermal-flow performance of humid air-water in the interspace outside staggered tube bundles. The formation of spray water film, heat and mass transfer process between humid air and spray water including spray water droplets and film were considered in this model. The influence of structure parameters was analyzed for thermal-flow performance of humid air-water in the interspace outside staggered tube bundles. It can be found that to increase the longitudinal and transverse distance between tube bundles can improve the heat transfer performance between spray water and wall of tube bundles, and decrease the pressure drop of humid air-water. But the mass transfer between spray water and humid air will only decrease with the transverse distance between tube bundles. Meanwhile, the relative humidity of humid air is not fully utilized at the top of staggered tube bundles when the transverse distance is more than 20 mm. Otherwise, the spray water will be lost heavily at the 19–24th rows of staggered tube bundles. The row number of staggered tube bundles should be reasonably designed in term of the transverse distance. The new correlations of heat transfer and pressure drop are also obtained in term of the simulation results. The Parker's correlation will be also recommended to design the mass transfer performance of that.